2022
DOI: 10.3390/toxics10020082
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of Chromium in Enchytraeus crypticus (Oligochaeta)

Abstract: Chromium is naturally occurring, but emission from anthropogenic sources can lead to increased soil concentrations. Information on its toxicokinetics is essential in order to understand the time needed to reach toxicity and the mechanisms of uptake/elimination. In this study the toxicokinetics of Cr(III) was evaluated using the soil standard species Enchytraeus crypticus. The animals were exposed to 180 mg Cr/kg dry soil, a sublethal concentration, in LUFA 2.2 natural soil. OECD guideline 317 was followed, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Cr in the +III and +VI oxidation states is a potential hapten in the development of contact allergy 62,63 . Prolonged exposure to Cr can cause skin ulcers, and severe redness and swelling of the skin 64 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cr in the +III and +VI oxidation states is a potential hapten in the development of contact allergy 62,63 . Prolonged exposure to Cr can cause skin ulcers, and severe redness and swelling of the skin 64 …”
Section: Resultsmentioning
confidence: 99%
“…62,63 Prolonged exposure to Cr can cause skin ulcers, and severe redness and swelling of the skin. 64 The detection of Fe, Zn, and Ti showed that our clay samples can be used as a suitable ingredient in the world of cosmetics. Moreover, red clay had a higher content of Fe than any other metal and consequently, higher potential for UVB protection as higher Fe content has been shown to significantly enhance the UV protection value of clays by reducing UVB-transmission levels.…”
Section: Metal Analysismentioning
confidence: 91%
“…Further studies using more advanced bioaccumulation methodologies, such as the one used by Santos et al (2022), are suggested to clarify the bioaccumulation potential. Also, the results in this paper, which are generated for Cd sourced from cadmium nitrate, might be interpreted for the other Cd sources such as cadmium chloride by referring to toxicokinetic and toxicodynamic of Cd (Santos et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The main aim of this study was to fill the gap in the literature by generating data for toxic concentrations and observing the accumulation of Cd as internal body concentrations in the presence of PS-MPs and biosolids. Further studies using more advanced bioaccumulation methodologies, such as the one used by Santos et al (2022), are suggested to clarify the bioaccumulation potential. Also, the FIGURE 4 Reproductive dose-response curve for Enchytraeus crypticus exposed to Lufa 2.2 soil mixed with cadmium, 0.5% polystyrene microplastics (PS-MPs), and 0.6 g biosolids results in this paper, which are generated for Cd sourced from cadmium nitrate, might be interpreted for the other Cd sources such as cadmium chloride by referring to toxicokinetic and toxicodynamic of Cd (Santos et al, 2022).…”
Section: Accumulation Of CD On E Crypticusmentioning
confidence: 99%
See 1 more Smart Citation